Putting the Squeeze on Plasmodesmata: A Role for Reticulons in Primary Plasmodesmata Formation. Issue 4 (17th June 2015) - Knox, Kirsten; Wang, Pengwei; Kriechbaumer, Verena; Tilsner, Jens; Frigerio, Lorenzo; Sparkes, Imogen; Hawes, Chris; Oparka, Karl
Abstract : Reticulon proteins involved in membrane curvature are targeted to the developing cell plate and label desmotubules in primary plasmodesmata. Abstract: Primary plasmodesmata (PD ) arise at cytokinesis when the new cell plate forms. During this process, fine strands of endoplasmic reticulum (ER ) are laid down between enlarging Golgi-derived vesicles to form nascent PD, each pore containing a desmotubule, a membranous rod derived from the cortical ER . Little is known about the forces that model the ER during cell plate formation. Here, we show that members of the reticulon (RTNLB) family of ER -tubulating proteins in Arabidopsis ( Arabidopsis thaliana ) may play a role in the formation of the desmotubule. RTNLB3 and RTNLB6, two RTNLBs present in the PD proteome, are recruited to the cell plate at late telophase, when primary PD are formed, and remain associated with primary PD in the mature cell wall. Both RTNLBs showed significant colocalization at PD with the viral movement protein of Tobacco mosaic virus, while superresolution imaging (three-dimensional structured illumination microscopy) of primary PD revealed the central desmotubule to be labeled by RTNLB6. Fluorescence recovery after photobleaching studies showed that these RTNLBs are mobile at the edge of the developing cell plate, where new wall materials are being delivered, but significantly less mobile at its center, where PD are forming. A truncated RTNLB3, unable to constrict the ER, was not recruited to the cell plate at cytokinesis. We discuss the potential roles of RTNLBs in desmotubule formation.